Bimetallic CuSbSe2: A Potential Anode Material for Sodium and Lithium‐Ion Batteries with High‐Rate Capability and Long‐Term Stability. Issue 6 (5th December 2022) - Hui, Da; Chen, Xi; Bian, Xiaofei; He, Chunfeng; Yao, Shiyu; Chen, Gang; Du, Fei
Abstract: Bimetallic transition metal chalcogenides (TMCs) materials have emerged as attractive anodes for lithium‐ion batteries (LIBs) and sodium‐ion batteries (SIBs) because of the high intrinsic electronic conductivity, rich redox sites and unique reaction mechanism. In this work, we report the synthesis and electrochemical properties of a novel bimetallic TMCs material CuSbSe2 . The as‐prepared anode delivers a high reversible capacity of 545.6 mA h g −1 for SIBs and 592.6 mA h g −1 for LIBs at a current density of 0.2 A g −1, and an excellent rate capability of 425.9 mA h g −1 at 20 A g −1 for SIBs and 226.0 mA h g −1 at 10 A g −1 for LIBs without any common‐used surface modification or carbonaceous compositing. In addition, ex situ X‐ray diffraction (XRD) and High‐resolution transmission electron microscopy (HRTEM) reveal a combined conversion‐alloying reaction mechanism of LIBs and NIBs. Our findings suggest bimetallic CuSbSe2 could be a potential anode material for both SIBs and LIBs. Abstract : Bimetallic CuSbSe2 are successfully synthesis and evaluated in sodium‐ and lithium‐ ion batteries. The CuSbSe2 anode exhibits superior rate behavior and cyclic performance. The excellent electrochemical property is attributed to the synergistic effect and the high electric conductivity of the material.